2013
DOI: 10.1051/epjconf/20134104018
|View full text |Cite
|
Sign up to set email alerts
|

Depth-dependent Detection Mechanisms of Coherent Phonons in n-type GaAs

Abstract: Abstract. Transient reflectivity measurements at different probing wavelengths reveal detection mechanisms of coherent phonon and phonon-plasmon coupled modes of n-doped GaAs to be strongly depth-dependent due to the carrier depletion at the surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Several groups have recently turned to time-resolved studies of the LOPC effect, with two main experimental thrusts. Petek and co-workers have demonstrated that the coupled LPP modes, owing to their Raman activity, can manifest as coherent oscillations observed through transient reflectivity measured with visible pulses. In a second thrust, several groups have measured the transient IR reflectivity from thicker films of SPhP materials, for which the LOPC effect appears as marked modifications to the Reststrahlen band and SPhP resonances. ,,, …”
Section: Resultsmentioning
confidence: 99%
“…Several groups have recently turned to time-resolved studies of the LOPC effect, with two main experimental thrusts. Petek and co-workers have demonstrated that the coupled LPP modes, owing to their Raman activity, can manifest as coherent oscillations observed through transient reflectivity measured with visible pulses. In a second thrust, several groups have measured the transient IR reflectivity from thicker films of SPhP materials, for which the LOPC effect appears as marked modifications to the Reststrahlen band and SPhP resonances. ,,, …”
Section: Resultsmentioning
confidence: 99%